Maternal Wnt/STOP signaling promotes cell division during early Xenopus embryogenesis - Huang, Ya-Lin; Anvarian, Zeinab; Döderlein, Gabriele; Acebron, Sergio P.; Niehrs, Christof (Proceedings of the National Academy of Sciences of the United States of America, 2015)
During Xenopus development, Wnt signaling is thought to function first after midblastula transition to regulate axial patterning via β-catenin-mediated transcription. Here, we report that Wnt/glycogen synthase kinase 3 (GSK3) signaling functions posttranscriptionally already in mature oocytes via Wnt/stabilization of proteins (STOP) signaling. Wnt signaling is induced in oocytes after their entry into meiotic metaphase II and declines again upon exit into interphase. Wnt signaling inhibits Gsk3 and thereby protects proteins from polyubiquitination and degradation in mature oocytes. In a protein array screen, we identify a cluster of mitotic effector proteins that are polyubiquitinated in a Gsk3-dependent manner in Xenopus. Consequently inhibition of maternal Wnt/STOP signaling, but not β-catenin signaling, leads to early cleavage arrest after fertilization. The results support a novel role for Wnt signaling in cell cycle progression independent of β-catenin.